(untitled) (Journal of Asian Development Studies, 2016)
This paper provides a comparative analysis of economic growth in Nigeria and South Korea. Both countries had similar levels of per capita income in the 1950s, used national development plans since 1962, and experienced democratic and military regimes. Today, South Korea’s per capita real income far exceeded those of Nigeria. This paper postulates that transformational leadership is one of the fundamental causes of the differences in per capita real income between both countries. This assertion is supported by examining and evaluating the leadership effectiveness in each country through their policy choices. The leaders in South Korea chose growth-enhancing policies while those leaders in Nigeria embraced ethnically biased distributional policies that contributed to ethnic resentment and regional division in Nigeria.